2021
DOI: 10.5763/kjsm.2021.39.3.102
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Athletes'; Attitudes toward Doping, Sport Orientation, and Perceived Motivational Climate in Sport among Collegiate Athletes

Abstract: This study aimed to identify the relationship between the attitudes toward doping, sport orientation, and perceived motivational climate in sport, and to provide useful information on the anti-doping strategy. Methods: A total of 567 athletes in 21 sports completed four questionnaires Performance Enhancement Attitude Scale (PEAS), Sport Orientation Questionnaire (SOQ; competitiveness orientation, win orientation, goal orientation), Task and Ego Orientation in Sport Questionnaire (TEOSQ; task orientation, ego o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…The gender differences in the PEAS scores between Korean and International studies can be understood in the viewpoint that athletes' attitudes toward doping and potential doping behaviors are influenced by various factors such as the diversity of the sporting environment in each country, participation rates, and competitive structures related to performance [29]. If it is accepted, it is plausible to explain that various environmental and contextual factors may affect attitudes toward doping, such as the increasing performance of female athletes in various sports and the intensification of competition [30,31]. In a previous meta-analysis of literature from various countries, male athletes had a PEAS mean score of 40.84 and female athletes had a PEAS mean score of 39.65, indicating that male athletes were more tolerant of doping [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gender differences in the PEAS scores between Korean and International studies can be understood in the viewpoint that athletes' attitudes toward doping and potential doping behaviors are influenced by various factors such as the diversity of the sporting environment in each country, participation rates, and competitive structures related to performance [29]. If it is accepted, it is plausible to explain that various environmental and contextual factors may affect attitudes toward doping, such as the increasing performance of female athletes in various sports and the intensification of competition [30,31]. In a previous meta-analysis of literature from various countries, male athletes had a PEAS mean score of 40.84 and female athletes had a PEAS mean score of 39.65, indicating that male athletes were more tolerant of doping [10].…”
Section: Discussionmentioning
confidence: 99%
“…In an environment of winning and record-breaking, athletes who want to exceed their physical capabilities are easily tempted to dope, rationalize that doping is necessary, and develop a tolerant attitude toward doping [30]. From a psychosocial perspective, lenient attitudes toward doping are considered to be associated with a higher likelihood of using banned substances [13].…”
Section: Discussionmentioning
confidence: 99%
“…Kim (2016) [28] (Individual, team) 164 male athletes from one university in Korea Correlation (r) MPS [5] MBI [22] Article Zhang (2021) [27] (Individual) 676 male and female tennis players aged 19 and above in Korea and China Correlation (r) MPS [5] ABQ [22] Dissertation Oh (2020) [37] (Individual) 268 male and female athletes registered in the Boxing Association of Korea in 2019 Correlation (r) MPS [5] ABQ [17] Dissertation Lee (2020) [38] (Individual) 302 male and female dancers in Korea Correlation (r) MPS [5] ABQ [17] Dissertation…”
Section: Type Of Publicationmentioning
confidence: 99%
“…For example, Ho et al [23] and Aghdasi [24], who used the MPS and ABQ, found negative results in the relationship between SOP and burnout; conversely, positive results were found in the relationship between SPP and burnout. Regarding OOP, which is the third factor of the MPS, Olsson et al [25] and Park [26] found a positive relationship between OOP and burnout, whereas Zhang [27] and Kim et al [28] found negative relationships, indicating that the results vary greatly among studies.…”
Section: Introduction 1research Purpose and Significancementioning
confidence: 98%
See 1 more Smart Citation